Determination of Employee Retention: Empirical Evidence from PT. ASDP Indonesia Ferry in Papua Province - Muh Arifai; Cahyono Saputra; Muh Asdar; Akbar Said; Sudiarti Dewi Kurra (Jurnal Administrasi Bisnis, 2026)
This study aims to analyze the factors that influence Employee Retention at the PT. ASDP Indonesia Ferry (Persero) Office in Merauke Regency, Papua Province. The factors studied include Organizational Components, Job Design, Rewards, Career Opportunities, and Employee Relations. The research method uses a quantitative approach with a survey through a questionnaire distributed to all 92 employees with a total sampling technique. The results of the normality test show that the residual data is normally distributed and is suitable for analysis with multiple regression. The simultaneous test (F test) shows a calculated F value of 11.969 with a significance of 0.000, which means that the five independent variables together have a significant effect on Employee Retention. The coefficient of determination (R Square) of 0.410 indicates that 41% of the variation in Employee Retention can be explained by the variables studied, while the remaining 59% is influenced by other factors outside this research model. Partially, Job Design, Rewards, and Employee Relations were shown to have a significant influence, with a significance value of 0.000 for Job Design and Rewards, and 0.027 for Employee Relations, respectively. These findings indicate that clear job design, fair rewards, and harmonious working relationships play a significant role in increasing employee retention.